2020
DOI: 10.1007/s11136-020-02439-z
|View full text |Cite
|
Sign up to set email alerts
|

Oral health-related quality of life of patients after heart transplantation and those with heart failure is associated with general health-related quality of life: a cross-sectional study

Abstract: The aim of this cross-sectional study was to examine the oral health-related quality of life (OHRQoL) in patients after heart transplantation (HTx) and those with heart failure (HF). Methods In total, 186 participants (HTx: 104, HF: 82) were recruited from the University Department for Cardiac Surgery, Leipzig Heart Centre, Germany. OHRQoL was assessed with the German short form of the oral health impact profile (OHIP-G14). Health-related quality of life (HRQoL) was evaluated using the short form 36 survey (SF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…The majority of studies (5/7) reported the short form of the "Oral Health Impact Profile" (OHIP 14) [23][24][25][26][27]. One study reported the long form (OHIP 49) [22], one study presented a self-composed "oral health quality score" Fig.…”
Section: Ohrqol Measurements and Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The majority of studies (5/7) reported the short form of the "Oral Health Impact Profile" (OHIP 14) [23][24][25][26][27]. One study reported the long form (OHIP 49) [22], one study presented a self-composed "oral health quality score" Fig.…”
Section: Ohrqol Measurements and Resultsmentioning
confidence: 99%
“…Two studies each revealed an association and/or correlation between OHRQoL and general health-related quality of life (HRQoL) [21,26], oral health parameters [21,22] or disease-related parameters [22,27]. Three studies reported OHRQoL subscales, whereby different subscales were applied (Table 5) [22,26,27].…”
Section: Ohrqol Measurements and Resultsmentioning
confidence: 99%
See 3 more Smart Citations